2016
DOI: 10.1007/s13277-016-5294-5
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer stem cell-specific markers and/or associated signaling pathways for overcoming cancer drug resistance

Abstract: Cancer stem cells (CSCs) are a small subpopulation of tumor cells with capabilities of self-renewal, dedifferentiation, tumorigenicity, and inherent chemo-and-radio therapy resistance. Tumor resistance is believed to be caused by CSCs that are intrinsically challenging to common treatments. A number of CSC markers including CD44, CD133, receptor tyrosine kinase, aldehyde dehydrogenases, epithelial cell adhesion molecule/epithelial specific antigen, and ATP-binding cassette subfamily G member 2 have been proved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 122 publications
0
20
0
1
Order By: Relevance
“…From this perspective, the specific targeting of CSCs, together with conventional chemotherapy or radiotherapy, may achieve stable remission or cure cancer. 43, 44 Auffinger et al 45 showed that therapeutic doses of TMZ consistently increased the glioma stem cells (GSC) pool both in vitro and in vivo , and provided the first evidence that chemotherapeutic agents can able to interconvert between non-GSCs and GSCs. Recent study of their group revealed this conversion of glioma cells dedifferentiation to glioma stem-like cells was attributed to the therapeutic TMZ stress-induced HIF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, the specific targeting of CSCs, together with conventional chemotherapy or radiotherapy, may achieve stable remission or cure cancer. 43, 44 Auffinger et al 45 showed that therapeutic doses of TMZ consistently increased the glioma stem cells (GSC) pool both in vitro and in vivo , and provided the first evidence that chemotherapeutic agents can able to interconvert between non-GSCs and GSCs. Recent study of their group revealed this conversion of glioma cells dedifferentiation to glioma stem-like cells was attributed to the therapeutic TMZ stress-induced HIF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of IC 50 evaluation, an RCC cell line demonstrating resistance to sunitinib, termed 786-O/S, was generated by serial treatment of the parental 786-O cell line with various concentrations of sunitinib from 2.5 to 10 µM at 37˚C with the dose given at 1 month intervals. Following continuous culture in the complete medium supplemented with 10 µM sunitinib for >10 passages, identify the IC 50 of 786O/S cells with method mentioned above (concentrations of sunitinib, 5,10,15,20,30,40 and 50 µM). The cells were employed as sunitinib-resistant RCC cells in all subsequent experiments.…”
Section: Determination Of the Half-inhibitory Concentration (Ic 50 ) mentioning
confidence: 99%
“…CSCs express several specific markers that may facilitate the isolation and identification of CSCs, including cluster of differentiation (CD) 133, which is widely expressed (14). CD133, also termed prominin 1, is a 120 kDa transmembrane glycoprotein that is recognized as a useful marker for the identification and isolation of CSCs from many types of solid tumors, including colon, brain, lung, liver, prostate, skin and kidney cancer (15).…”
Section: Introductionmentioning
confidence: 99%
“…While much of the discussion has been towards genetic changes within the tumor and that different cells may have different mutations, one has to wonder whether there are also epigenetic mechanisms that are seen in the cells within the tumor and if this is different depending on the immediate microenvironment of the tumor cells. One such cell that could be a real problem is the CSC, which is potentially the cause for treatment failure, drug resistance, metastasis and recurrence after surgery, chemotherapy as well as radiotherapy[206]. We [9] have learned that CSCs might have signaling pathways that are potentially unique to them such as Wnt/β-catenin, and Notch etc.…”
Section: Discussionmentioning
confidence: 99%